Band‐pass filter‐like antenna validation in an ultra‐wideband in‐car wireless channel. Issue 4 (1st March 2015) - J. Garcia Zuazola, Ignacio; Azpilicueta, Leire; Sharma, Ashwani; Landaluce, Hugo; Falcone, Francisco; Angulo, Ignacio; Perallos, Asier; Whittow, William G.; Elmirghani, Jaafar M.H.; Batchelor, John C.
Abstract : Ultra‐wideband (UWB) is a very attractive technology for innovative in‐car wireless communications requiring high data rates. A designated antenna, which presents a reflection coefficient (S11) matched band comparable to the band‐pass filter (BPF) normally required at the transducers, plays a positive contribution in this in‐car application and was validated for the scenario. The inherited BPF‐like response of the antenna relaxes the specification of the front‐end BPF components of the transceivers. The in‐car propagation channel was modelled and used to validate the BPF‐like antenna. For the modelling, a comprehensive set of well‐defined measurements (using a standard antenna) were used to set‐up the in‐car channel simulator and simulated results were used to validate the BPF‐like antenna. In addition, the performance of the UWB radio system is studied and the probability of errors over the communication channel compared using the standard and the BPF‐like antenna by predictions.